Removal Of Arsenic From Water Using Natural Coagulant (Moringa Oliefera) - Mezughi, Khaled M (2003)
Tin industry was once a major contributor to the Malaysian economy as Malaysia was the world's largest tin-producing country, from the 1950s to 1980s. As the mining practice used was mainly surface mining, large mine pools were left behind. The pools are contaminated with the heavy metals, especially arsenic from naturally occurring minerals in excess from the mining. When the cities expand and the need for more building ground arises, ex-tin mining pools will be filled with construction site waste or other available discards and built upon. Arsenic contamination of drinking water is a world-wide problem. Long term exposure to arsenic via drinking water leads to wide range of health problems including: skin cancer, gangrene of the limbs, vascular diseases, conjunctivitis, central nervous system damage and hyperkeratosis. Coagulation flocculation and sedimentation is widely used for water treatment. Alum, as the common coagulant used in this process can lead to rise in the pH which requires further treatment for pH adjustment prior to discharge, besides its low ability for As (III) removal. Therefore, alternative coagulants have been investigated. Moringa oleifera is considered as one of the environmentally friendly coagulant used in turbidity removal. In this study, coagulation and flocculation process using M. Oleifera seeds and alum followed by sedimentation was used to compare their abilities for As (III) removal. In this experimental setup, the concentration of coagulant, initial As (Ill) levels and pH were varied to study their effect on As (Ill) removal. The mixing speeds (rapid and slow) were fixed at 100 and 40 rpm for 2 and 20 minutes, respectively, and the sedimentation time used was 30 minutes. While As (Ill) removal using alum, as coagulant was less than 10%, M. Oleifera achieved very high As (Ill) removal. At initial concentration of 0.5 ppm arsenic, 1000 and 2000 mg/l of M. Oleifera were able to remove 91.9 and 95.8 % of arsenic respectively. The As (III) residual level achieved in this study complied with the Malaysian Standard Drinking Water, which permits level for 0.05 ppm of arsenic. At higher initial As (Ill) concentrations of 2.0 and 3.0 ppm, 4000 and 5000 mg/l of M. Oleifera were able to remove 97 and 96.8 % of arsenic, respectively. The residual level of As (Ill) complied with the Malaysian Standard Discharge Water which permits level for 0.1 ppm of arsenic. When the concentration of initial arsenic was increased to 5.0 and 10.0 ppm, 1000 and 1500 mg/l of M. Oleifera removed 70.4 and 65.6 % of arsenic, respectively. Although, the residual level of As (Ill) was higher than the permitted discharge level, perhaps due to the high concentrations of As (Ill), the removal achieved is noticeably higher than that achieved by alum. The results showed that M. Oleifera is a promising natural polymer for removing heavy metals from the ground water.